The Importance of RRR in Cadastral System - Manandhar, Sanjaya; Manandhar, Bijaya Kumar; Upadhyaya, Pradeep Sapkota; Dahal, Tanka Prasad (Journal on Geoinformatics, Nepal, 2018)
Cadastral System is the base platform to abstracting land rights; maintain its ecords and registration. It normally makes agreements with dispersed right interests as enure security, continuum of land rights, registration system, adjudication process and de-facto, local and central government policy aspects within land dministration party. As, RRRRights, Restrictions and Responsibilities are related to spatial unit and its owner, normally right contains ownership and tenure aspect whereas restrictions is related to control use and different activities on land. Responsibilities relate more to a social, environmental, communal, ethical obligation or defiance to environmental sustainability. Most cadastral system of developing countries are still absence in identifying and assigning clear RRR in certain spatial unit i.e. buffered on Highways, banks of Rivers and Streams and special cases of shade of High-tension-transmission lines etc. This paper aims to provide an overall understanding of such RRR cases with the concept of cadastral system. This paper aims to show AS-IS situation cadastral system with comparing TO-BE condition with gap analysis based on LADM conception of some related cases. This paper concludes that cadastral system will be good when there is clearly defined RRR. So, better identification and assignment of RRR between spatial unit and land administration party can support better cadastral system which supports to better land administration of country.